Manifestations of Lithuanianness in Latvian Literature of the First Half of the 20th Century: Stereotypical and Unusual - Butkus, Vigmantas (Acta humanitarica academiae Saulensis, 2024)
The article is based on the theoretical approach suggested by literary imagology, drawing an assumption that the image that is revealed in fiction of one country about the other country, the nation is not a literary value that is solely enclosed inside a text, but it rather often reflects specific historical, geographical, social, economic, cultural and other realia, too. There is a large number of literary pieces which depict the Lithuania-related topic or single Lithuanian motifs in Latvian literature of the first half of the 20th century; therefore, the article limits itself with analysis of only a part of them in the chosen aspect of imagology. Around thirty authors of the said period who wrote pieces of various genres, including both famous names, who became classics and less known authors, are discussed. Majority of these literary pieces reveal such manifestations of Lithuanianness which can be considered as trite, stereotypical because they are repeated, obtain new semantic, emotional shades in various contexts; nevertheless, they always retain almost the same notional core. The ethnotype of a Lithuanian beggar (Latv. leišu nabags / ubags) is one of the most frequently occurring manifestations of such kind; it reflects a historical, economic situation of the second half of the 19th century – first half of the 20th century, when many people from Lithuania would go begging in Latvia. The fiction also quite frequently and highly variously displays the motif of Lithuanian neighbourhood, its geographical proximity. The motifs of “a Lithuanian cherry” (Latv. leišu ķirsis) and “a Lithuanian goose” (Latv. leišu zoss) are much rarer, though repeating in fiction works related to specific agrarian and culinary realia prevailing in Latvia at that time. An image of a disastrous “quagmire of Lithuania” (Latv. leišu muklājs) that was made popular by a composer Alfrēds Kalniņš’s (1879–1951) song based on a verse by a poet Atis Ķeniņš (1874–1961) ought to be considered as dissociated from objective realia; this image had a metaphorical meaning which was usually directly unrelated to Lithuania. Manifestations of the topic of Lithuania which are characteristic of some exclusiveness, unusualness, even some kind of cultural exoticism in Latvian literature of that time are relatively sparse. The article analytically presents five pieces of fiction that display quite detailed portraits of atypical, unordinary characters from Lithuania. The most suggestive of them is an image of a Jewish man, named Perec, from Lithuanian province, who was educated under the influence of the religious spirit of the Torah but eventually embraced the truths of Marxism, and his milieu, created by a famous leftist writer Andrejs Kurcijs (the true name Andrejs Kuršinskis, 1884–1959) in his short story “The God of Paupers” (“Nabago dievs”, 1929).